(untitled) (Journal of Economic Research & Business Administration, 2015)
According to its becoming concept the strategic management has faced with concepts such as information collection, budgeting, costs, cost optimization. These areas help to create a single picture as when negotiating a general introduction to the development of the organization, and taking into account the quality and cost. The aim of the article is the consideration of the theoretical foundations of strategic management in conjunction with the strategic account. For this is given the controversy of the authors, they examine the emergence of strategic management, strategic cost accounting methods, and strategic accounting. Nowadays, the research area of strategic management includes all of the tools of this type of control. If we have considered earlier only some models that take into account the life cycle of a firm, the goods, today the market requires including in the tools of strategic management the issues such as cost accounting, business process optimization, cost optimization, building of a balanced scorecard, and strategic accounting of regulatory costs. In this context, strategic accounting acts as a special tool for strategic management.